Influence of Public Service Announcements on Primary Health Care Delivery in Nigeria - Ifeanyi M. Nwokeocha; Uwem, A. Akpan (Jurnal Multidisiplin Madani, 2023)
This paper examined the influence of public service announcements on primary healthcare delivery in Nigeria. The study adopted the explorative  research method which reviewed literatures by scholars as related to this study. Two empirical reviews were understudied, the theory of reasoned action and social marketing theory were adopted and studied. The study recommended that all government should review their financial allocations to health care delivery in line with global best practices . High priority programmes for primary healthcare should be considered and additional  resources that may be available deployed, more staff should be trained and increase in wages for those who will agree to serve in the area, effective public service announcements messages should also be strategically planned by communicators to influence behaviours; etc